“Aku Istimewa, Aku Bisa”: Membaca Permulaan Bahasa Inggris melalui Metode Fonik bagi Anak Speech Delay - Munggaraning Westhisi, Sharina (Al-Athfal: Jurnal Pendidikan Anak, 2020)
Speech delay becomes a phenomenon for children such as in English pre-reading instruction for non-native English speaker, thus it is needed a proper method for them. This study aims to identify the implementation of phonics method that used in an English pre-reading instruction for a child with speech delay. This study uses a case study which involves one teacher and one child with speech delay. The data obtained by interviewing a teacher and parents, observing the child, and identifying lesson plans. Thematic analysis is used to determine relevant themes of the topic. The results show each instruction has one objective, focuses on letters’ sound and spelling spelling two up to four sounds of a word, and a child could utter words clearly. Additionally, interactions with peers encourage a child to be competitive and enthusiastic. Furthermore, phonics method might be an alternative method for children with speech delay to acquire English pre-reading skills, especially in Early Childhood Education (ECE).